Implementation of Video Tracker Application for Measurement of Elastic Pendulum Oscillatory Motion - Sigit Ristanto; Hafizh Aji Prakosa; Nur Khoiri; Affandi Faisal Kurniawan; Joko Saefan (Pendidikan Fisika UIN Alauddin Makassar, 2024)
Advances in technology have a huge impact on the development of physics, the tracker application is one example of technological developments in the field of physics that can solve problems in analysing videos of the motion of an object recorded using a smartphone. One of the motion phenomena that can be analysed using the tracker application is the oscillatory motion of an elastic pendulum. The purpose of this research to know the analysis of elastic pendulum motion in the form of oscillation trajectory and period using tracker application. The method used in this research is experimental method. The results of the analysis obtained from this research are that the oscillation trajectory of the elastic pendulum does not move the same or irregularly when oscillating, and the period that occurs in the oscillation of the x and y axes against time (t) is relatively constant.